On deviance and loving nature a case study of the ecological activism of greenpeace Philippines - Alvarez, Maria Khristine O. (Philippine Sociological Review, 2010)
This paper examines notions of deviance by looking at the strategy of direct action employed by Greenpeace Philippines in its environmental activism. The environmental movement is often considered a more peaceful social movement. However, in the West, where direct actions by radical ecological grassroots movements are sometimes violent, environmental activism has come to be synonymous with eco-terrorism. While the methods employed by Greenpeace are always nonviolent, this deviant identification is nevertheless retained. Such astigma is prevalent mainly in North America and Western Europe, but has not been as readily extended to Green Peace Philippines. This paper shows how the organization has actually been repeatedly forgiven for its deviant direct actions, as evinced, for instance, by the rarity of legal action filed against Greenpeace Philippines and its activists. This research in progress puts forward a more positive understanding of deviance - as an expression of agency and a concrete manifestation of love for nature. As a strategy, deviance has been crucial to the transformative character of Greenpeace as an organization.